Hair‐pulling disorder (Trichotillomania): Etiopathogenesis, diagnosis and treatment in a nutshell. Issue 1 (15th October 2020) - Torales, Julio; Ruiz Díaz, Noelia; Ventriglio, Antonio; Castaldelli‐Maia, João Mauricio; Barrios, Iván; García, Oscar; Navarro, Rodrigo; González‐Urbieta, Israel; O'Higgins, Marcelo; Jafferany, Mohammad
Abstract: Hair‐pulling disorder (Trichotillomania) is a disabling mental disorder. Patient's behavior is characterized by the recurrent pulling of own hair with hair loss and a marked dysfunction in various areas of daily life. Trichotillomania is a relatively common disorder with pediatric onset, often associated with significant morbidity, comorbidity, and functional decline. Surprisingly, children or adolescents have been little studied in the research studies on the pathophysiology and psychopathology of trichotillomania. Furthermore, more evidences regarding the effective and evidence‐based pharmacological interventions for the treatment of this condition are encouraged. This narrative review will report on the etiopathogenesis and clinical manifestations of trichotillomania including criteria for diagnosis and treatment issues of this complex mental disorder.